2019
DOI: 10.1177/2309499019839023
|View full text |Cite
|
Sign up to set email alerts
|

After-hours elective spine deformity corrective surgery for patients with Adolescent Idiopathic Scoliosis: Is it safe?

Abstract: Objective: The aim of this study was to compare the outcome of after-hours electively planned Posterior Spinal Fusion surgeries for Adolescent Idiopathic Scoliosis (AIS) patients with daytime surgeries. Methods: This was a retrospective propensity score-matched study using prospectively collected data. Surgeries performed between 08:00 and 16:59 h were labeled as daytime surgeries (group 1) and surgeries performed between 17:00 and 06:00 h were labeled as after-hours surgeries (group 2). The perioperative outc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The authors performed a propensity score matching using patients' and surgical characteristics and created two groups according to the time of surgery (08:00-16:59 daytime; 17:00-06:00 after-hours). 1 They did not find any difference in terms of surgical outcome, intraoperative blood loss and length of hospitalization. The authors concluded that this type of surgery performed during after-hours is as safe as during daytime.…”
mentioning
confidence: 90%
“…The authors performed a propensity score matching using patients' and surgical characteristics and created two groups according to the time of surgery (08:00-16:59 daytime; 17:00-06:00 after-hours). 1 They did not find any difference in terms of surgical outcome, intraoperative blood loss and length of hospitalization. The authors concluded that this type of surgery performed during after-hours is as safe as during daytime.…”
mentioning
confidence: 90%
“…Our study investigated a specific subset of adolescent idiopathic scoliosis (AIS) patients who had planned elective posterior spinal fusion (PSF) surgeries and not emergency surgeries. 2 Moreover, our patients had surgeries done by a dedicated spine team involving the same surgeons, anaesthetist, radiographers, nurses and assistants. Therefore, the aim of our study and the patient population of our study were not similar to the study done by Cortegiani et al…”
mentioning
confidence: 99%